THE IMPACT OF DIRECT FOREIGN INVESTMENTS ON EMPLOYMENT - THE CASE OF NORTH MACEDONIA - Dervis, Bulent; Agai-Lochi, Emrije (International Scientific Journal Vision, 2022)
The beginning of foreign direct investments into a country with the capital enables the entry of new technology. Yet, with the production of foreigners in the country on the one hand reduces the dependence on the other, ie imports, on the other hand increases the export capacity of the country. Foreign investors’ operating in the country, means the establishment of new companies and the creation of new business areas. North Macedonia is the lowest cost per worker in the region. In order to attract foreign investments, Northern Macedonia has minimized the social security shares paid to the worker. However, the introduction of new investments has been encouraged by reducing the cost of social security and tax, which is financially burden for foreign and domestic investors. Revenues and institutions are among the conveniences applied to encourage foreign investors, tax exemptions and discounts, rawage imports and other customs duties, and regulations in the labor market. When we look at Northern Macedonia, especially between 2007 and 2020, foreign investors have provided many convenience to ensure that foreign investments enter the country. In recent years, a noticeable increase has been achieved in foreign investments. In the face of all these developments, the activities of foreign companies in the country, whether directly dependent on production or in the service sector, increased the employment and reduced unemployment. According to the data of the Macedonian Statistical Institute, the unemployment rate in the country in 2010 was approximately 37 percent, while in 2021, this rate decreased to 15 percent. Although the decrease in unemployment is attributed to foreign investments, especially the policies of the fight against unemployment implemented by the government.